PENDIDIKAN NASIONAL, GLOBALISASI DAN PERANAN KELUARGA - Afdhal Afdhal (JURNAL GEOGRAFI, 2014)
Abstract This present essay strives to shed a light on the implications of globalisation on Indonesia’s national education. Itelaborates two central question: (1) Is Indonesia’s education already functioning to play a part in the globalisation? (2) What are the toughest abstacles to the contemporary Indonesia’s education and options introuncing the challenges? It subsequently offers an alternative that is the roles of family intitution in minimising the inpacts of the estructive-side of the glabalisation as well as helping the goverment and schooling institutions to provide better educational services